2013
DOI: 10.1063/1.4813446
|View full text |Cite
|
Sign up to set email alerts
|

Strain-induced defects as nonradiative recombination centers in green-emitting GaInN/GaN quantum well structures

Abstract: The origin of the green gap for GaInN/GaN quantum wells is investigated via temperature-dependent time-resolved photoluminescence spectroscopy. A strong correlation between nonradiative lifetimes and total strain energy is observed, although the wells are almost fully strained. We discuss this observation in terms of nonradiative recombination at defects which contribute to a beginning partial relaxation. The formation energy of a defect is likely reduced by the amount of its released strain energy. We therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 17 publications
3
53
1
Order By: Relevance
“…Basically, the green-gap problem originates from the higher indium mole fraction in the GaInN quantum-well active region of green LEDs. The higher mole fraction increases the lattice mismatch with the adjacent GaN cladding layers and so the defect density, increases the mechanical strain [6] and the consequent quantum-confined Stark effect [7], and decreases thermal stability because of the decreased melting temperature [8]. Therefore, higher nonradiative and lower radiative recombination rates are expected, which lead to lower internal quantum efficiency (IQE) in longer wavelength LEDs with the higher indium mole fraction.…”
Section: Introductionmentioning
confidence: 96%
“…Basically, the green-gap problem originates from the higher indium mole fraction in the GaInN quantum-well active region of green LEDs. The higher mole fraction increases the lattice mismatch with the adjacent GaN cladding layers and so the defect density, increases the mechanical strain [6] and the consequent quantum-confined Stark effect [7], and decreases thermal stability because of the decreased melting temperature [8]. Therefore, higher nonradiative and lower radiative recombination rates are expected, which lead to lower internal quantum efficiency (IQE) in longer wavelength LEDs with the higher indium mole fraction.…”
Section: Introductionmentioning
confidence: 96%
“…If the non-radiative recombination pathways are similar then it can be anticipated that the efficiency of green light emission would be less than that of blue emission. However, it has been reported 8,9 that this change in the radiative recombination lifetime is not sufficient to fully explain the reduction in efficiency. It has been suggested that there is also a reduction in the non-radiative recombination lifetime.…”
mentioning
confidence: 99%
“…It is anticipated that this increase in the radiative recombination lifetime in green emitting samples leads to less efficient competition with non-radiative recombination pathways, resulting in the reduction in EQE for green LEDs. However it has been suggested that this increase in radiative recombination lifetime alone is not sufficient to explain the extent to which the EQE is reduced in green emitting devices [8,9], and that the effects of non-radiative recombination must also be increased.…”
mentioning
confidence: 99%